Pemikiran Ekonomi Islam Pada Masa Daulah Mamluk - Mardiah, Siti Maryam; Wahyuningsih, Sefti; Parakassi, Idris; Siradjuddin (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This study provides a brief overview of the Mamluk Dynasty, including its background, origins, contributions, and the economic thought that developed under its rule. The Mamluk state emerged as a result of the military slavery system that developed in the 13th century, with its leaders originating from slaves who were bought and trained to become soldiers. This dynasty made significant contributions in the fields of politics, military, and economy, creating stability in the Middle East, promoting trade, and encouraging urbanization. Economic thought during the Mamluk period also highlighted the important roles of agriculture, trade, and the tax system, which supported the sustainability of the government.